PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 17 BATANG DUKUp - Riati Riati; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The low yield learn science of students class IV SD Negeri 17 Batang Duku that background of this research. This is evident from the 20 students who completed only 6 people (30%) while 14 is not finished (70%) with average result 57,95. This is due teacher still use traditional teaching methods. The reason from this research is for improve learning outcomes grade science students class IV SD Negeri 17 Batang Duku with applying cooperative learning model team assisted individualization (TAI) type. This research held SD Negeri 17 Batang Duku with subject students class IV that is 8 man and 12 woman. Research design that is classroom action research that is two cycle with 4 stages that is planning, implementation, observation and reflection. The cycle 1 the first meeting activites teachers percentage 58,33% category enough,at the second meeting increase percentage 66,67% category best. For cycle 2 the third meeting akctivities teacher 75,00% catgory best and fourth meeting activities increase become 87,50% category vry good. Whil activities students first meeting in cycle 1 with percentage 54,16% category enough and second meeting percentage 62,50% category best. The cycle 2 third meeting percentage increase 70,82% category best and fourth meeting percentage 83,30% category very good. For result study basic score result studies average is 57,95. In cycle 1 of the average increase 66,25 with increase percentage result 14,32% from basic skor to UH1. For cycle 2 of the average result increase 73,73 with increase percentage result 27,26%.Keyword : Cooperative model team assisted individualization (TAI), learning result of science